Examining the Relationships Between Islamic Governance, Financial Performance, and Corporate Value: A Literature Review - Arnez Cendana; Muhammad Kiki Januar; Tantina Haryati; Acynthia Ayu Wilasittha; Sofie Yunida Putri (Nusantara Science and Technology Proceedings, 2023)
The objective of this literature review is to offer a thorough examination of the relationship between Islamic company Social Responsibility (ICSR), Islamic Corporate Governance (ICG), financial performance, and company value in the realm of Islamic finance and business practices. The main aim of this study is to conduct a comprehensive literature analysis to obtain a deeper understanding of the interconnected elements that play a role in the overall achievement and long-term viability of Islamic enterprises. The research technique utilized for this review entails a comprehensive analysis of pertinent scholarly literature, with a specific emphasis on the concepts and implementation of ICSR (Islamic Corporate Social Responsibility) and ICG (Islamic Corporate Governance) within the context of Islamic ethics and adherence to Sharia. The evaluation emphasizes the importance of ensuring that company actions are by Islamic principles, such as engaging in philanthropy, practicing ethical business conduct, and demonstrating environmental responsibility. Additionally, the literature review presents empirical findings that suggest organizations that are dedicated to the principles of corporate social responsibility (CSR) and corporate governance (CG) tend to demonstrate greater financial performance and increased corporate value. This study examines the potential impact of these principles on the long-term financial performance and stability of Islamic markets, with a specific focus on enhancing shareholder wealth. The paper additionally examines several approaches and indicators employed for evaluating ICSR (Islamic Corporate Social Responsibility), ICG (Islamic Corporate Governance), financial performance, and corporate value within Islamic settings. It acknowledges the distinct difficulties encountered by scholars and practitioners when attempting to effectively assess these categories. The literature review has two implications. First and foremost, this highlights the significance of incorporating practises related to Islamic Corporate Social Responsibility (ICSR) and Islamic Corporate Governance (ICG) within the framework of Islamic firms, with a focus on their ability to enhance financial performance and corporate value. Additionally, this underscores the necessity for additional study in order to establish standardized measuring frameworks and methodologies specifically designed for Islamic banking and commercial contexts. This literature study offers significant insights into the intricate interconnections between ICSR (Islamic Corporate Social Responsibility), ICG (Islamic Corporate Governance), financial performance, and corporate value within the context of Islamic business practises. This statement highlights the need of ensuring that Islamic principles are in accordance with business actions and governance structures, in order to promote the well-being of stakeholders and ensure the long-term viability of Islamic firms. Future study should prioritise the resolution of measurement issues and the examination of the intricacies inherent in these associations among distinct Islamic sectors and geographical areas.